A Percutaneous Portal Vein Puncture Under Artificial Ascites for Intraoperative Hepatic Segmentation Using Indocyanine Green Fluorescence: A Technical Report of Laparoscopic Anatomic Liver Resection. Issue 2 (9th April 2022) - Kasai, Meidai; Aihara, Tukasa; Ikuta, Shinichi; Nakajima, Takayoshi; Yamanaka, Naoki
Abstract : Background: Laparoscopic liver resection have developed and is widely spread as standard procedure in these days, however, laparoscopic anatomic liver resection is still challenging, especially for posterosuperior lesions because of difficulties in segmental mapping and surgical techniques. Recently, the positive staining and negative staining method using fluorescent imaging techniques have been reported from experienced Asian centers, allowing to identify the tumor-bearing portal territory to be resected including the posterosuperior segment in laparoscopy. Those techniques are applicable in some cases; hence, it remains the room for improvement to establish as a feasible approach. Herein, we describe a percutaneous tumor-bearing portal vein puncture method under artificial ascites after the pneumoperitoneum for laparoscopic segmentectomy for segment 8. Case Presentation and Surgical Procedure: A male patient in his 60s was admitted for an incidentally diagnosed hepatic mass in segment 8. Findings of the computed tomography scan showed a 2.5-cm-sized hepatocellular carcinoma lesion. Then, laparoscopic anatomic liver resection for segment 8 was planned. The segmentation of the segment 8 was performed through a percutaneous tumor-bearing portal vein puncture using indocyanine green injection with extracorporeal ultrasound guidance under artificial ascites. According to indocyanine green fluorescence navigation, anatomic liver resection was completed. Operative time was recorded as 375 minutes. The estimated intraoperative blood loss was 50 mL without the requirement for an intraoperative transfusion. The planned resections were successful with histologically negative surgical margins. The patient was discharged on the 19th postoperative day with normal liver function test results. There was no operation-related complication during hospitalization. Conclusion: The intraoperative percutaneous portal vein puncture method under artificial ascites was useful for the identification of posterosuperior segment in laparoscopic anatomic segmentectomy.